Comparison of the self-expanding Evolut-PRO transcatheter aortic valve to its predecessor Evolut-R in the real world multicenter ATLAS registry. (1st July 2020) - Kalogeras, Konstantinos; Ruparelia, Neil; Kabir, Tito; Jabbour, Richard; Naganuma, Toru; Vavuranakis, Manolis; Nakamura, Sunao; Wang, Brian; Sen, Sayan; Hadjiloizou, Nearchos; Malik, Iqbal S.; Mikhail, Ghada; et al.
Abstract: Background: The Evolut PRO self-expanding transcatheter aortic valve has been designed to feature an outer pericardial wrap that aims to reduce paravalvular regurgitation (PVR) rates. Medium-term clinical outcomes, compared to its predecessor Evolut R, in a real-world setting, have not been investigated. The aim of the present study was to compare the two valves with regards to peri-procedural complications, early outcomes and mid-term survival. Methods: Consecutive patients, undergoing TAVI with either the Evolut PRO or Evolut R device, from the multicenter ATLAS registry were retrospectively studied. Outcomes studied included periprocedural complications, PVR at discharge, need for new pacemaker implantation and Kaplan-Meier estimated 1-year all-cause mortality. Results: Analysis included 673 patients (498 treated with Evolut R and 175 treated with Evolut PRO). At least moderate PVR was numerically lower amongst patients treated with Evolut PRO (7.4% vs 3.8% for Evolut R and Evolut PRO respectively, p = .108). Rates of new permanent pacemaker (PPM) implantation (21.1% vs. 11.9%, p = .023), and bail-out valve-in-valve (2.4% vs. 0%, p = .049) were significantly lower amongst the Evolut PRO group. No differences were demonstrated regarding bleeding, stroke or acute kidney injury. One-year Kaplan-Meier estimated survival was similar between groups (93% for Evolut R vs. 91.2% for Evolut PRO, plog-rank = 0.806). Conclusions: The Evolut PRO self-expanding valve demonstrates similar mid-term survival rates and numerically, yet not significant, lower incidence of PVR compared to its predecessor. Interestingly this new generation valve is associated with a significantly reduced rate for new PPM implantation. Future studies are required to confirm this finding. Highlights: Last generation Evolut PRO features an outer pericardial wrap aiming to reduced PVR It demonstrates similar mid-term survival rates compared to its predecessor. Last generation device demonstrates, yet not significant, lower incidence of PVR. Significantly reduced rate of new PPM implantation has been recorded.